89.3k views
11 votes
Answers for both boxes please for 25 points!​

Answers for both boxes please for 25 points!​-example-1

2 Answers

13 votes

Answer:

(-2,6)

Explanation:

3x + 2y = 6

-3x + y = 12

3x + -3x = 0

2y + y = 3y

6 + 12 = 18

3y = 18

3y/3 = 18/3

y = 6

-3x + y = 12

-3x + 6 = 12

-3x = 12 - 6

-3x = 6

-3x/-3 = 6/-3

x = -2

Check the graph for proof

Answers for both boxes please for 25 points!​-example-1
User Kagetoki
by
6.1k points
8 votes

Answer:

Explanation:

you just need to add both equations

you will get 3y=12+6=18

3y=18

y=6

now replace y=6

3x+12=6

3x=6-12

3x=-6

x=-2

(-2,6)

User Oleg Yablokov
by
5.4k points